A Comparison of the Effectiveness of Audio and Visual Learning Media in Improving Student Learning Outcomes - Dery Kurniawan; Dini Fitrianti; Fitri Nur Alya; Hasna Daiyah Islami; Putri Wardani; Sania Alifah; Yuliyanti Yuliyanti (Journal of Contemporary Pedagogy and Learning Science, 2026)
This study aimed to compare the effectiveness of audio and visual learning media in improving students’ learning outcomes. The research employed a quantitative experimental method with a pretest–posttest group design. The sample consisted of 60 eighth-grade students at SMP Negeri 6 Kota Serang, divided equally into an audio group and a visual group through randomization. The research instrument initially comprised 10 multiple-choice items, which were tested for validity prior to implementation. Based on item analysis, four items were declared valid, three items were revised, and a total of seven items were used in both the pretest and posttest. Normality testing using the Kolmogorov–Smirnov test indicated that most data were not normally distributed, leading to the use of the Wilcoxon Signed-Rank Test for hypothesis testing. The results showed that the audio group experienced a significant improvement in learning outcomes (p = 0.005 < 0.05), while the visual group showed no significant improvement (p = 0.390 > 0.05). These findings indicate that audio learning media is more effective than visual learning media in enhancing students’ learning outcomes.